2010
DOI: 10.1111/j.1365-3059.2010.02276.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effect of interactions between disease control, nitrogen supply and land use change on the greenhouse gas emissions associated with wheat production

Abstract: A method for calculating the effect of disease control on greenhouse gas (GHG) emissions associated with wheat production, reported previously, was developed further to account for effects of disease control on the amount of fertilizer nitrogen (N) which should be applied and on changes in land use. Data from nine randomized and replicated field experiments from the UK and Denmark showed that the economic optimum N input to winter wheat was greater if diseases were controlled by fungicides, than for untreated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 23 publications
5
27
0
Order By: Relevance
“…At Ridgetown and Lucan in 2010, the maximum yields were produced with N rates between 100 to 170 kg N ha -1 with the T123 fungicide treatment; yields declined at the highest rate of N where no fungicides were applied (likely in part due to lodging and harvest losses at these two sites). The difference in response between the UTC and the T3 and T123 fungicide treatments suggests that the most economical rate of N may vary with efficacy of disease control by fungicides, as reported by others (Olesen et al, 2003a;Berry et al, 2010).…”
Section: ---------------------------% Severity † --------------------mentioning
confidence: 77%
“…At Ridgetown and Lucan in 2010, the maximum yields were produced with N rates between 100 to 170 kg N ha -1 with the T123 fungicide treatment; yields declined at the highest rate of N where no fungicides were applied (likely in part due to lodging and harvest losses at these two sites). The difference in response between the UTC and the T3 and T123 fungicide treatments suggests that the most economical rate of N may vary with efficacy of disease control by fungicides, as reported by others (Olesen et al, 2003a;Berry et al, 2010).…”
Section: ---------------------------% Severity † --------------------mentioning
confidence: 77%
“…These differences are the consequences of different cultivation systems. In organic farming, farmers do not apply mineral fertilizers and pesticides, therefore GWP is lower than A -small farms, B -medium farms, C -large farms [17]. The performed analysis shows that GHG emissions per hectare depend on farm size and ranged from 2,378 kg CO 2 eq.…”
Section: Current Environmental Characterizationmentioning
confidence: 97%
“…Khoshnevisan et al [18] reported total emissions of 2,711.58 kg CO 2 eq.·ha -1 for wheat production. In Berry et al [17] studies, GHG emissions were very strongly influenced by the N fertilizer rate and disease control, and ranged from 1,498 to 4,176 kg CO 2 eq.·ha -1 . Therefore, it is very important to define optimum doses of agricultural inputs in order to limit unnecessary outlays and decrease emissions.…”
Section: Current Environmental Characterizationmentioning
confidence: 99%
“…Soil moisture in the days prior to fertilizer application can also be important in influencing emissions (Dobbie et al 1999). Berry et al (2010) suggested that the application of N early in the growing season (i.e., February-March) when soil temperatures are generally low may reduce the potential for N 2 O loss. However, this approach would need to be balanced against the greater risk of increased NO À 3 leaching if significant rainfall were to occur following fertilizer application to soils close to field capacity.…”
Section: Improved Timing Of Mineral Fertilizer N Applicationmentioning
confidence: 99%